Docetaxel-Induced Lung Injury: An Under-Recognized Complication of a Commonly Used Chemotherapeutic Agent - Manuprasad, Avaronnan; Ganesan, Prasanth; Mahajan, Vandana; Ganesan, Trivadi S; Radhakrishnan, Venkatraman; Dhanushkodi, Manikandan; Sagar, Tenali Gnana (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Docetaxel-induced pneumonitis is a rare, but potentially serious complication of a commonly used chemotherapeutic agent. Methods: We performed an audit of patients with suspected docetaxel pneumonitis from the tertiary cancer center. Results: Out of 477 patients who received docetaxel over a 1 year period, eight patients (1.7%) developed lung injury. All patients (median age: 43 years [34–65]) had breast cancer (four metastatic on palliative docetaxel, two were on neoadjuvant, and two were on adjuvant therapy) and had received a median of three cycles of docetaxel 75 mg/m2 in a 3 weekly schedule (7 as single agent and 1 in combination with cyclophosphamide). One patient had the preexisting pulmonary disease (localized bronchiectasis), and four had received prior radiation to the chest wall or dorsal spine. The median time from administration of the last dose was 16 days (8–28). Most (n = 6/8, 75%) required hospitalization. Three patients with CTCAE Grade 3 pneumonitis required oxygen support. Radiology showed a pattern of interstitial pneumonitis in most patients. All the patients responded to steroids and follow-up imaging showed resolution of infiltrates. The median duration of hospital stay was 8.5 days (7–18 days). There was no mortality due to this condition. Conclusions: Drug-induced lung injury should be considered in patients presenting with respiratory symptoms after administration of docetaxel. Timely initiation of steroids could reduce complications.
Keywords: Breast cancer; docetaxel; pneumonitis; steroids